2016
DOI: 10.1038/srep39573
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Hepatic Adaptation to Chronic Cholestasis induced by Primary Sclerosing Cholangitis

Abstract: Pathogenesis of primary sclerosing cholangitis (PSC) may involve impaired bile acid (BA) homeostasis. We analyzed expressions of factors mediating enterohepatic circulation of BA using ileal and colonic (ascending and sigmoid) biopsies obtained from patients with PSC with and without ulcerative colitis (UC) and explanted PSC livers. Two-fold increase of BA-activated farnesoid X receptor (FXR) protein levels were seen in ascending and sigmoid colon of PSC patients with correspondingly decreased apical sodium-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
1
25
1
Order By: Relevance
“…End-stage PSC and DC patients both demonstrate enrichment in conjugated forms of chenodeoxycholic acid in their portal serum. This is consistent with the reduction in microsomal sterol 12α-hydroxylase (CYP8B1) levels that have previously been observed in the setting of PSC cirrhosis [ 29 ]. Conversely, some secondary bile acids are decreased in both PSC and DC cohorts, suggesting a reduction in the microbial population capable of bile salt hydrolase and other secondary bile acid enzymatic activities.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…End-stage PSC and DC patients both demonstrate enrichment in conjugated forms of chenodeoxycholic acid in their portal serum. This is consistent with the reduction in microsomal sterol 12α-hydroxylase (CYP8B1) levels that have previously been observed in the setting of PSC cirrhosis [ 29 ]. Conversely, some secondary bile acids are decreased in both PSC and DC cohorts, suggesting a reduction in the microbial population capable of bile salt hydrolase and other secondary bile acid enzymatic activities.…”
Section: Discussionsupporting
confidence: 90%
“…Studies in nonalcoholic liver disease demonstrate that FFAs can disrupt short heterodimer partner (SHP)-induced FXR activation, leading to the upregulation of NTCP and CYP7A1, thereby permitting unregulated bile acid synthesis and subsequent hepatic injury [ 31 ]. In PSC, there is a lack of CYP7A1 suppression despite high levels of SHP and FXR gene expression, supporting the presence of dysregulated SHP signaling [ 29 ]; however, this may not be a generalizable feature of PSC, as very low levels of serum C4 (an indicator of CYP7A1 enzymatic activity) were detected in the advanced stages of PSC [ 32 ]. The elevated levels of FFAs may indicate possible defects in β-oxidation, which is also enabled by FXR as well as peroxisome proliferator-activated receptor-alpha (PPAR-α) [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most laboratory species, including the mouse, rat, and hamster, the distribution of ASBT in the intestine is limited to the terminal ileum. In humans, however, ASBT also is expressed in the duodenum and colon at both mRNA and protein levels. In our study, low mRNA levels of ASBT were observed in the proximal small intestine (ie, duodenum and jejunum), but ASBT protein was not detected in these segments.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic effects of bile upon cholangiocytes [32,45], due to cholestasis, or primary or secondary changes in bile composition as part of disease processes in the bile ducts or colon [46][47][48][49][50], or impairment of protective means (e.g. the so-called ''bicarbonate umbrella'') [51], may contribute to biliary inflammatory and fibrotic processes.…”
Section: Pathophysiological Basis Of Therapymentioning
confidence: 99%